Tarihî Süreç İçerisinde Felsefî Bir Kavram Olarak Anarşizm - Cengiz Çuhadar (Dini Araştırmalar, 2015)
This article aims to give information about the definition of anarchism and it’s short history. Anarchism is a word open to misunderstanding. It must not be confused with terror. Anarchism refers to a social philosophy in which there exists no state (government), rule or authority in general. It claims to be a social philosophy against all administrative institutionalization. Despite its common features, because of interpretation and methodical differences, it has some different variations. In spite of this variety, the anarchists agree upon a non-governmental understanding of society